Development of Visual Media Uses Geogebra Application on Linear Program Material - Rani Sugiarni; Sabina Haikal Aulia; Afila Mangaraja Butar (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
The research is aimed at developing mathematical visual media with the help of the GeoGebra Application on linear program material that tests its validity and practicality. This research uses the development research method with ADDIE design, but developed in this research is the GeoGebra Application to Linear Program Materials. Participants in to see this validation by 2 experts and 32 high school students in Cianjur district. Research procedures include analysis, design, development, implementation and evaluation. The instruments used are validation sheets and practicality. Based on the results of the research showed that the application of GeoGebra on the linear program material of the validator results is good and validated and practical at the time students use it.